Preparation method of modified graphene self-healing anticorrosive paint

Through the preparation method of modified graphene self-healing anticorrosion coating, the problem of existing graphene anticorrosion coatings is solved, and the problem of easy corrosion at room temperature is achieved, better electrochemical impedance performance and self-healing effect are achieved, and the service life of the coating is extended.

CN119899571APending Publication Date: 2025-04-29JIUJIANG FIRE EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411913148.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing graphene anticorrosion coatings are prone to react with the metal matrix at room temperature to accelerate corrosion. When the coating undergoes corrosion and cracking, the conductivity increases sharply, limiting its large-scale application in the field of marine anticorrosion coatings.

Method used

The preparation method of modified graphene self-healing anticorrosion coating was adopted. By dispersing graphene with p-phenylenediamine in N,N-dimethylformamide solution, and then adding sodium nitrite to react in an ice bath to form amide graphene. Polyaniline passivation graphene and its benzotriazole supported anticorrosion coating were prepared by reacting with aniline, ammonium persulfate and benzotriazole. Finally, it was mixed with epoxy resin to prepare modified graphene self-healing anticorrosion coating.

Benefits of technology

Modified graphene self-healing anticorrosion coatings have greatly improved electrochemical impedance performance and have ideal self-healing effects, which can effectively extend the service life of the coating on the protective substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899571A_ABST
    Figure CN119899571A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a modified graphene self-healing anticorrosive coating, which comprises the following steps: S1, dispersing graphene and p-phenylenediamine in an N, N-dimethylformamide solution, and carrying out ultrasonic dispersion to obtain a dispersion liquid; s2, adding sodium nitrite into the dispersion liquid, and carrying out an ice bath reaction to obtain a mixed solution; s3, filtering and drying the mixed solution to obtain solid residues, and drying the solid residues in a vacuum freeze dryer for 36 hours to obtain aminated graphene; s4, stirring the aminated graphene, aniline, ammonium persulfate and benzotriazole to obtain polyaniline passivated graphene and a benzotriazole-loaded anticorrosive material of the polyaniline passivated graphene; s6, mixing and stirring epoxy E44 resin, an organic solvent and a curing agent to obtain epoxy organic emulsion; and S7, mixing and stirring the polyaniline passivated graphene, the benzotriazole-loaded anticorrosive material of the polyaniline passivated graphene and the epoxy organic emulsion to obtain the modified graphene self-healing anticorrosive coating. According to the invention, not only is the electrochemical impedance performance greatly improved, but also an ideal self-healing effect on repairing a damaged coating is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] The invention relates to the technical field of marine anti-corrosion coating preparation, and in particular to a method for preparing a modified graphene self-healing anti-corrosion coating. Background Art

[0003] Marine corrosion can cause damage and loss of function of various marine engineering infrastructure and equipment, shorten their service life, and cause huge waste of resources, materials and energy; it can also lead to sudden disasters, trigger oil and gas leaks, pollute the marine environment, and even cause casualties.

[0004] At present, among a series of measures taken to address marine corrosion, coating the protected metal surface with graphene anti-corrosion coatings has received extensive attention in the technical field. However, at room temperature, the electrical conductivity of graphene is , the carrier migration rate reaches This provides favorable conditions for the conduction of electrons between graphene and the metal matrix, and the special two-dimensional wrinkled structure and large specific surface area of ​​graphene create a large amount of storage space for the transportation of electrons; at the same time, because the potential of graphene is lower than the self-corrosion potential of metal, the two are very likely to produce anode and cathode reactions (graphene as cathode and metal as anode), accelerating local corrosion; when the coating corrodes and cracks, O2 and H2O in the environment penetrate into the coating defects, causing the conductivity of the coating to increase sharply, thereby showing obvious graphene-metal microgalvanic corrosion. This phenomenon limits the large-scale application of graphene in the field of marine anti-corrosion coatings. Summary of the invention

[0005] In order to solve the above-mentioned deficiencies in the prior art, the present invention proposes a method for preparing a modified graphene self-healing anti-corrosion coating.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing a modified graphene self-healing anti-corrosion coating, comprising the following steps: S1. dispersing graphene and p-phenylenediamine in an N,N-dimethylformamide solution, wherein the mass ratio of graphene, p-phenylenediamine and N,N-dimethylformamide solution is 1:1:2, and obtaining a dispersion by ultrasonic dispersion; S2, adding sodium nitrite to the dispersion and reacting in an ice bath for 16-24 hours, wherein the mass ratio of sodium nitrite to graphene is 1:1, to obtain a mixed solution; S3, washing the mixed solution with deionized water and anhydrous ethanol, filtering it, and vacuum drying it at 60° C. for 10 h to obtain a solid residue, and drying the solid residue in a vacuum freeze dryer for 36 h to obtain amino graphene; S4, stirring the aminated graphene, aniline, ammonium persulfate and benzotriazole to obtain polyaniline-passivated graphene and an anti-corrosion material loaded with benzotriazole; S6, mixing and stirring the epoxy E44 resin, the organic solvent and the curing agent to obtain an epoxy organic emulsion, wherein the mass ratio of the epoxy E44 resin, the organic solvent and the curing agent is 1:1:0.5; S7. The polyaniline-passivated graphene and the anti-corrosion material loaded with benzotriazole are mixed and stirred with the epoxy organic emulsion to obtain the modified graphene self-healing anti-corrosion coating.

[0007] Preferably, the preparation method of polyaniline passivated graphene and its anti-corrosion material loaded with benzotriazole comprises the following steps: A. Slowly add the amination graphene and aniline solution into N,N-dimethylformamide and stir for 1-1.5 hours to obtain a mixed solution, wherein the mass ratio of the amination graphene and aniline solution to N,N-dimethylformamide is 1:1; B. Fully dissolving ammonium persulfate in N,N-dimethylformamide to obtain a dispersion, wherein the mass ratio of ammonium persulfate to N,N-dimethylformamide is 1:1; C. The mixed solution and the dispersion were stirred continuously for 2-4 hours under an ice bath temperature of -15°C to obtain a dark green product. The dark green product was washed and filtered in sequence and then dried under vacuum for 10 hours to obtain a polyaniline-modified amino graphene product. D. Ultrasonic dispersion of benzotriazole in N,N-dimethylformamide to obtain a BTA dispersion with a mass fraction of 6%; E. Add the polyaniline-modified amino graphene product to the BTA dispersion and stir for 24 hours. After stirring, place the mixture in a vacuum box and let it stand for 10 hours to obtain a mixed solution, so that BTA can be fully loaded on the surface of the product. F. The mixed solution is filtered and dried in sequence to obtain polyaniline-modified amino graphene and its loaded benzotriazole material.

[0008] Preferably, step S7 further includes: Silane coupling agent, dispersant and film-forming aid are added to polyaniline-modified amino graphene and its loaded benzotriazole material, epoxy organic emulsion and defoamer are added after stirring for a period of time, and stirring is continued. After stirring, centrifugation is performed to eliminate bubbles, and polyamide curing agent 650 is added. After stirring, a modified graphene self-healing anti-corrosion coating is obtained, which is the final product.

[0009] Preferably, the mass ratio of polyaniline-modified amino graphene and its loaded benzotriazole material, silane coupling agent and dispersant, film-forming aid, epoxy organic emulsion, defoamer and polyamide curing agent 650 is 5:1:2:3:15:2:30-100.

[0010] Preferably, the silane coupling agent is one of KH550, KH570, KH-792, A-151, Si-602 and Si-563 or a combination thereof.

[0011] Preferably, the dispersant is one of HR-4030, DS-193, HR-7102 and HR-4103 or a combination thereof.

[0012] Preferably, the film-forming aid is one of SD-505 and FZ3667 or a combination of the two.

[0013] Preferably, the defoaming agent is one of BYK-A530, sh-550, DS8750, KS-603, M5600 or a combination thereof.

[0014] Preferably, the curing agent is one of dodecyl maleic anhydride, hexahydrophthalic anhydride, phthalic anhydride, imidazole, dicyandiamide, boron trichloride-monoethylamine complex, triethanolamine and boron trichloride benzylamine, or a combination thereof.

[0015] Compared with the prior art, the present invention has been found through performance testing that, compared with conventional marine anti-corrosion coatings, the modified graphene self-healing anti-corrosion coating prepared by the present invention not only has greatly improved electrochemical impedance performance, but also has an ideal self-healing effect on repairing damaged coatings. It can be seen that the coating prepared by the present invention has a better anti-corrosion effect and is applied in the field of marine anti-corrosion, which can effectively extend the service life of the coating on the protective substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the electrochemical impedance spectrum of the composite coating from 24h to 72h.

[0017] Figure 2 This is the electrochemical impedance spectrum of the composite coating from 84h to 96h.

[0018] Figure 3 This is the electrochemical impedance spectrum of pure epoxy coating for 24h-28h.

[0019] Figure 4 Electrochemical impedance spectroscopy of pure epoxy coating for 72h-90h DETAILED DESCRIPTION

[0020] The invention is described in detail below with reference to the accompanying drawings and embodiments. Example

[0021] The present invention provides a method for preparing a modified graphene self-healing anti-corrosion coating, comprising the following steps: S1. Dispersing graphene and p-phenylenediamine in N,N-dimethylformamide solution, wherein the mass ratio of graphene, p-phenylenediamine and N,N-dimethylformamide solution is 1:1:2, and obtaining a dispersion by ultrasonic dispersion, wherein the ultrasonic dispersion time is 0.5 h; S2, adding sodium nitrite to the dispersion and reacting in an ice bath for 24 hours, the ice bath temperature is -15°C, the mass ratio of sodium nitrite to graphene is 1:1, and obtaining a mixed solution; S3, washing the mixed solution with deionized water and anhydrous ethanol, filtering it, and vacuum drying it at 60° C. for 10 h to obtain a solid residue, and drying the solid residue in a vacuum freeze dryer for 36 h to obtain amino graphene; S4, stirring the aminated graphene, aniline, ammonium persulfate and benzotriazole to obtain polyaniline-passivated graphene and an anti-corrosion material loaded with benzotriazole; S6, mixing and stirring the epoxy E44 resin, the organic solvent and the curing agent to obtain an epoxy organic emulsion, wherein the mass ratio of the epoxy E44 resin, the organic solvent and the curing agent is 1:1:0.5; S7. Add silane coupling agent (KH550, KH570 and KH-792), dispersant (HR-4030, DS-193 and HR-7102) and film-forming aid (SD-505) to the polyaniline-modified amino graphene and its loaded benzotriazole material, stir for a while, add epoxy organic emulsion and defoamer and continue stirring, centrifuge to eliminate bubbles after stirring, add polyamide curing agent 650, and stir to obtain modified graphene self-healing anti-corrosion coating. The mass ratio of polyaniline-modified amino graphene and its loaded benzotriazole material, silane coupling agent and dispersant, film-forming aid, epoxy organic emulsion, defoamer and polyamide curing agent 650 is 5:1:2:3:15:2:65.

[0022] The preparation method of polyaniline passivated graphene and anti-corrosion material loaded with benzotriazole comprises the following steps: A. Slowly add the amination graphene and aniline solution into N,N-dimethylformamide and stir for 1-1.5 hours to obtain a mixed solution, wherein the mass ratio of the amination graphene and aniline solution to N,N-dimethylformamide is 1:1; B. Fully dissolving ammonium persulfate in N,N-dimethylformamide to obtain a dispersion, wherein the mass ratio of ammonium persulfate to N,N-dimethylformamide is 1:1; C. The mixed solution and the dispersion were stirred continuously for 3 h under an ice bath temperature of -15 °C to obtain a dark green product. The dark green product was washed and filtered in sequence and then dried under a vacuum state of 60 °C for 10 h to obtain a polyaniline-modified amino graphene product. D. Ultrasonic dispersion of benzotriazole in N,N-dimethylformamide to obtain a BTA dispersion with a mass fraction of 6%; E. Add the polyaniline-modified amino graphene product to the BTA dispersion and stir for 24 hours. After stirring, place the mixture in a vacuum box and let it stand for 10 hours to obtain a mixed solution, so that BTA can be fully loaded on the surface of the product. F. The mixed solution is filtered and dried in sequence to obtain polyaniline-modified amino graphene and its loaded benzotriazole material.

[0023] In order to evaluate the self-healing and anti-corrosion effect of the modified graphene self-healing anti-corrosion coating, the prepared modified graphene self-healing anti-corrosion coating and pure epoxy coating were coated on the coating according to the preparation method of Example 1 (hereinafter referred to as the composite coating), and the EIS measurement of the scratch test was performed on it. In the scratch test, the scratched pure epoxy coating was used as a control example.

[0024] Figure 1-Figure 2 The electrochemical impedance spectra of the scratched composite coating are shown in Figure 2 for 24h, 48h, 72h, 84h, 90h, and 96h immersion time. It can be seen from the figure that the coating has two different spectra in these two time periods. Figure 1 The time period spectrum in the graph shows a double capacitive reactance arc. Figure 2 The spectrum of the time period in the graph shows that the high-frequency region is a capacitive reactance arc, and the low-frequency region is a diffusion straight line with a slope of nearly 45°, indicating that the failure time of this composite coating is 96h. Figure 3-Figure 4 In the experiment, for the pure epoxy coating with scratches, the spectra in the time periods of immersion time of 24h, 48h, 72h, 84h, and 90h were consistent, all of which were straight lines of nearly 45°. After immersion for 90h, the spectra were closest to the straight line, at which time the pure epoxy coating had failed, showing a complete Weber diffusion process. Therefore, from the results, the anti-corrosion coating obtained by the present invention provides a longer protection time when the coating is damaged, and has better performance than the pure epoxy coating on the market.

[0025] The protective effect of the composite coating of the present invention comes from two aspects. One is the barrier effect of the filler itself in the coating. The other is the dynamic protective effect of the composite coating on the substrate surface. The substance further chelates with the corrosive metal ions to generate products, or is directly adsorbed on the metal surface. Due to the effects of these two processes, a protective layer capable of blocking the invasion of corrosive media is obtained on the substrate surface. The spectrum ( Figure 1 , Figure 2) also indirectly reflects the release and effect of BTA, making the intrusion resistance of H2O and Cl- in the composite coating much greater than that in the epoxy coating; further, the self-healing performance of the composite coating can also be reflected from the impedance value of the scratch test. In the scratch test, the |Z|0.01HZ values ​​of the composite coating after immersion for 24h and 48h were 1.0×107(Ω·cm2) and 4.18×106(Ω·cm2), respectively. Compared with the undamaged coating, the impedance value did not change significantly, indicating that the composite coating has excellent self-healing performance.

[0026] The anti-corrosion effect of the composite coating obtained by the present invention comes from two aspects. On the one hand, it comes from the shielding effect of the special two-dimensional layered plane structure of graphene on the corrosive medium, which effectively enhances the protective effect of the damaged external coating; on the other hand, the benzotriazole loaded on the surface of the graphene is an excellent corrosion inhibitor, which is a fibrous substance soluble in water. When it is desorbed from the surface of the graphene filler and dissolved in water, it diffuses into the damaged composite coating through Brownian motion. Since the H atoms of the primary amine are more active and easily oxidized and replaced, the N atoms form lone pairs of electrons, so that the metal ions (with empty d orbitals) that can cause anodic corrosion on the surface of the substrate, such as Fe 2+ Complexation forms a protective layer to prevent H2O, Cl - diffusion; at the same time, due to the strong adsorption effect of benzotriazole, when it penetrates into the metal surface in the form of solution, it will form an adsorption protective layer.

[0027] During the preparation process, the role of stirring is, on the one hand, to improve the dispersion effect of polyaniline passivated graphene and its anti-corrosion materials loaded with benzotriazole, so that they are evenly dispersed inside the coating and increase their grafting rate with the resin matrix, such as promoting the grafting reaction between the epoxy groups of the resin and the amino groups of graphene and benzotriazole; on the other hand, during the stirring process, the reaction rate between the epoxy resin and various additives and promoters is accelerated, thereby increasing the crosslinking density and degree of polymerization inside the coating, further improving the density of the coating.

[0028] Under the premise that no conflict occurs, those skilled in the art may freely combine and superimpose the above-mentioned additional technical features.

[0029] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the patent and protection scope of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a modified graphene self-healing anti-corrosion coating, characterized in that: The following steps are involved: S1. dispersing graphene and p-phenylenediamine in an N,N-dimethylformamide solution, wherein the mass ratio of graphene, p-phenylenediamine and N,N-dimethylformamide solution is 1:1:2, and obtaining a dispersion by ultrasonic dispersion; S2, adding sodium nitrite to the dispersion and reacting in an ice bath for 16-24 hours, wherein the mass ratio of sodium nitrite to graphene is 1:1, to obtain a mixed solution; S3, washing the mixed solution with deionized water and anhydrous ethanol, filtering it, and vacuum drying it at 60° C. for 10 h to obtain a solid residue, and drying the solid residue in a vacuum freeze dryer for 36 h to obtain amino graphene; S4, stirring the aminated graphene, aniline, ammonium persulfate and benzotriazole to obtain polyaniline-passivated graphene and an anti-corrosion material loaded with benzotriazole; S6, mixing and stirring the epoxy E44 resin, the organic solvent and the curing agent to obtain an epoxy organic emulsion, wherein the mass ratio of the epoxy E44 resin, the organic solvent and the curing agent is 1:1:0.5; S7, mixing and stirring the polyaniline-passivated graphene and the anti-corrosion material loaded with benzotriazole and the epoxy organic emulsion to obtain a modified graphene self-healing anti-corrosion coating.

2. The method for preparing a modified graphene self-healing anti-corrosion coating according to claim 1, characterized in that: The preparation method of polyaniline passivated graphene and anti-corrosion material loaded with benzotriazole comprises the following steps: A. Slowly adding the amination graphene and aniline solution into N,N-dimethylformamide and stirring for 1-1.5 hours to obtain a mixed solution, wherein the mass ratio of the amination graphene and aniline solution to N,N-dimethylformamide is 1:1; B. Fully dissolving ammonium persulfate in N,N-dimethylformamide to obtain a dispersion, wherein the mass ratio of ammonium persulfate to N,N-dimethylformamide is 1:1; C. The mixed solution and the dispersion were continuously stirred for 2-4 hours under an ice bath temperature of -15°C to obtain a dark green product. The dark green product was washed and filtered in sequence and then dried under vacuum for 10 hours to obtain a polyaniline-modified amino graphene product. D. Ultrasonic dispersion of benzotriazole in N,N-dimethylformamide to obtain a BTA dispersion with a mass fraction of 6%; E. Add the polyaniline-modified amino graphene product to the BTA dispersion and stir for 24 hours. After stirring, place the mixture in a vacuum box and let it stand for 10 hours to obtain a mixed solution, so that BTA can be fully loaded on the surface of the product. F. Performing filtering-drying steps on the mixed solution in sequence to obtain polyaniline-modified amino graphene and its loaded benzotriazole material.

3. The method for preparing a modified graphene self-healing anti-corrosion coating according to claim 1, characterized in that: The step S7 further includes: A silane coupling agent, a dispersant and a film-forming aid are added to the polyaniline-modified amino graphene and the benzotriazole-loaded material thereof, and after stirring for a period of time, epoxy organic emulsion and a defoaming agent are added and the stirring is continued. After stirring, the bubbles are eliminated by centrifugation, and then a polyamide curing agent 650 is added. After stirring, a modified graphene self-healing anti-corrosion coating is obtained, and the modified graphene self-healing anti-corrosion coating is the final product.

4. A method for preparing a modified graphene self-healing anti-corrosion coating as claimed in claim 3, characterized in that: The mass ratio of the polyaniline-modified amino graphene and its loaded benzotriazole material, silane coupling agent and dispersant, film-forming aid, epoxy organic emulsion, defoamer and polyamide curing agent 650 is 5:1:2:3:15:2:30-100.

5. The method for preparing a modified graphene self-healing anti-corrosion coating according to claim 3, characterized in that: The silane coupling agent is one of KH550, KH570, KH-792, A-151, Si-602 and Si-563 or a combination thereof.

6. A method for preparing a modified graphene self-healing anti-corrosion coating according to claim 3, characterized in that: The dispersant is one of HR-4030, DS-193, HR-7102 and HR-4103 or a combination thereof.

7. A method for preparing a modified graphene self-healing anti-corrosion coating according to claim 3, characterized in that: The film-forming aid is one of SD-505 and FZ3667 or a combination of the two.

8. The method for preparing a modified graphene self-healing anti-corrosion coating according to claim 3, characterized in that: The defoamer is one of BYK-A530, sh-550, DS8750, KS-603, M5600 or a combination thereof.

9. The method for preparing a modified graphene self-healing anti-corrosion coating according to claim 3, characterized in that: The curing agent is one of dodecyl maleic anhydride, hexahydrophthalic anhydride, phthalic anhydride, imidazole, dicyandiamide, boron trichloride-monoethylamine complex, triethanolamine and boron trichloride benzylamine, or a combination thereof.